Integrasi Metode Active Learning dalam Penguatan Nilai-Nilai Islami pada Pembelajaran PAI - Riswadi, Riswadi; Amarullah, Zen; Ulum, Bachrul (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study examines how active learning strengthens Islamic values in Islamic Education (PAI) classrooms, addressing the long-standing dominance of cognitive-oriented instruction. Using a qualitative descriptive design, data were gathered through interviews with teachers and students, classroom observations, and document analysis. Findings show that active learning promotes deeper engagement with religious concepts and facilitates the internalization of Islamic values such as honesty, discipline, responsibility, and cooperation. Collaborative and contextual learning activities successfully foster a participatory classroom climate that supports continuous value formation. Theoretically, this study reinforces the relevance of student-centered pedagogies in value-based learning. Practically, it highlights the need for teachers to design activity-rich lessons that integrate character formation. Future research is recommended to develop evaluation models grounded in Islamic values to balance cognitive, affective, and psychomotor outcomes.